Business development of pineapple derivative product at KUBE Mega Buana in Jambi Province - zakiah; Selin Naberta; Siti Kurniasih; Fuad Muchlis; Vika Indah Rahayu (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2026)
Pineapple derivative product business at KUBE Mega Buana during Covid-19 experience a decline. There needs to be business development so that business activities can continue after Covid-19. The purpose of this study is to describe the level of development of pineapple derivative product business among KUBU Mega Buana members. This research was conducted in Tangkit Village, Sungai Gelam District, Jambi Province. The selection of respondents used the census method with the number of respondents being 30 members of KUBE Mega Buana. Data collection methods use primary data and secondary data. The data analysis method uses descriptive. The results of the study indicate that the development of pineapple derivative product businesses at KUBE Mega Buana is classified as having a high category at the initiation stage of 71,60%, at the elaboration stage of 75,08%, at the monetization stage 76,75%, and at the sustainability & innovation stage of 72,89%